THE MEDIATING IMPACT OF GENDER IN THE RELATIONSHIP OF LEADERSHIP AND SUPPLY CHAIN MANAGEMENT OF TEXTILE INDUSTRY IN INDONESIA - Mardiana, Nova (International Journal of Supply Chain Management, 2020)
The current study purpose is to examine the mediating impact of gender in the relationship of leadership and supply chain management of textile industry in Indonesia. For this purpose, the data was collected from the 350 middle managers by using a simple random sampling technique which yield a 50 percent response rate. The Structural Equation Modeling (SEM) of the study has shown that leadership has a positive and significant relationship with the supply chain management and gender. In addition, the gender also has a positive and significant relationship with the supply chain management. On the other hand, the indirect effect of the study also shown that gender is significantly and positively mediates in the relationship of leadership and supply chain management. Therefore, this mediating effect is considered to be a big contribution of the study which could become a new area of research in future. The research limitations and future directions of the study also stated at the end of the study.